Pengaruh Social Influence Terhadap Minat Menggunakan Media Sosial Melalui Sikap Generasi Z di Kota Palembang - Sopian, Valensia; Siega, Stephen; Edsu, Steven; Fansyuri, R. Gilbert T; Taneddy, Rainaldy Reyhan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study examines the effect of social media influences on generation Z's attitude when using social media in Palembang City. The result of this study is to determine the correlation coefficient of the independent effect of the independent variable on the dependent variable through mediating variables. This research uses the quantitative method with the form of correlation and SmartPLS 4 as a tool to manage the data, whereas the data collection uses a questionnaire via Google Form with 87 respondents. Purposive sampling is used for determining the sample with the condition that the respondent in Generation Z in Palambang City actively uses social media. The result of this study showed that the coefficient of determination of direct influence is greater than that of indirect influence. In conclusion, there's no effect of social influences on generation Z's attitude when using social media in Palembang City.